Newer technique in surfactant administration - Wandita, Setya (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2023)
Respiratory distress syndrome (RDS) is a morbidity often found in premature infants. The incidence of RDS is inversely proportional to gestational age and decreases with the presence of antenatal steroids. Surfactant is a phospholipid produced by type 2 pneumatocytes. Surfactant coats the alveoli and bronchioles so that their surface tension is reduced. Thus, the alveoli and bronchioli remain open, allowing gas exchange. After surfactants are known to benefit RDS, the next question is when is the right time to give them. There are 2 alternative times for surfactant therapy, namely before symptoms appear or a diagnosis is made (prophylaxis) and after RDS symptoms appear (rescue). Several Newer techniques in surfactant administration will be discussed in this article.